(untitled) (Vietnam Journal of Community Medicine, 2024)
Purpose: To compare the effects of Desflurane and Sevofurane on early anesthesia recovery in patients undergoing to craniotomy for brain tumor. Methods: The study included 60 patients aged 18-70 years who had ASA physical statuses of I-II and were scheduled for brain tumor surgery. Patients were randomly divided into two groups: Desflurane and Sevofurane. Anaesthesia was routinely induced in all patients followed by Desflurane 5-6% or Sevofurane 1,5-2% to maintain BIS in 40-60. Emergence time was measured as the time from drug discontinuation to the time at which patients opened their eyes; tracheal extubation, the incidence of hemodynamic events, pain, nausea, and shivering requiring rescue medication was recorded. Results: The recovery time of group Desflurane is faster than that of group Sevoflurane: group Desflurane’s breathing time is 6.2 ± 2.0 minutes compared to 7.5 ± 1.5 minutes of group Sevoflurane, time to open eyes of group Desflurane was 7.8 ± 1.9 minutes compared to 10.2 ± 2.1 minutes of group Sevoflurane, the time to withdraw extubation of group Desflurane was 9.1 ± 2.1 minutes compared to 13.3 ± 2.5 minutes of group Sevoflurane. However, there was no difference between the two groups in the rates of pain, vomiting, nausea, chills or hemodynamic events between the two groups. Conclusion: Patients who received Desflurane had a shorter extubation and recovery time but similar intraoperative and postoperative incidence of complications compared with those who received Sevofurane.